A study in a Polish ataxia cohort indicates genetic heterogeneity and points to MTCL1 as a novel candidate gene. Issue 3 (8th January 2019) - Krygier, Magdalena; Kwarciany, Mariusz; Wasilewska, Krystyna; Pienkowski, Victor Murcia; Krawczyńska, Natalia; Zielonka, Daniel; Kosińska, Joanna; Stawinski, Piotr; Rudzińska‐Bar, Monika; Boczarska‐Jedynak, Magdalena; Karaszewski, Bartosz; Limon, Janusz; et al.
Abstract : Inherited ataxias are a group of highly heterogeneous, complex neurological disorders representing a significant diagnostic challenge in clinical practice. We performed a next‐generation sequencing (NGS) analysis in 10 index cases with unexplained progressive cerebellar ataxia of suspected autosomal recessive inheritance. A definite molecular diagnosis was obtained in 5/10 families and included the following diseases: autosomal recessive spastic ataxia of Charlevoix‐Saguenay, POLR3B ‐related hypomyelinating leukodystrophy, primary coenzyme Q10 deficiency type 4, Niemann‐Pick disease type C1 and SYNE1 ‐related ataxia. In addition, we found a novel homozygous MTCL1 loss of function variant p.(Lys407fs) in a 23‐year‐old patient with slowly progressive cerebellar ataxia, mild intellectual disability, seizures in childhood and episodic pain in the lower limbs. The identified variant is predicted to truncate the protein after first 444 of 1586 amino acids. MTCL1 encodes a microtubule‐associated protein highly expressed in cerebellar Purkinje cells; its knockout in a mouse model causes ataxia. We propose MTCL1 as a candidate gene for autosomal recessive cerebellar ataxia in humans. In addition, our study confirms the high diagnostic yield of NGS in early‐onset cerebellar ataxias, with at least 50% detection rate in our ataxia cohort. Abstract : We performed next‐generation sequencing analysis in 10 index cases with unexplained progressive cerebellar ataxia of suspected autosomal recessive inheritance. A definite molecular diagnosis was obtained in 5/10 families and included the following diseases: autosomal recessive spastic ataxia of Charlevoix‐Saguenay, POLR3B ‐related hypomyelinating leukodystrophy, primary coenzyme Q10 deficiency type 4, Niemann‐Pick disease type C1 and SYNE1 ‐related ataxia. In addition, we found a novel homozygous MTCL1 loss of function variant (Hg19:chr18:008784328‐CA>C, NM_015210.3:c.1220delA, p.(Lys407fs)) in a 23‐year‐old patient with slowly progressive cerebellar ataxia, mild intellectual disability, seizures in childhood and episodic pain in the lower limbs. Patient's sagittal T2‐weighted magnetic resonance imaging demonstrates isolated atrophy of the cerebellar vermis and perivermal region. The identified variant is predicted to truncate the protein after first 444 of 1586 amino acids. MTCL1 encodes a microtubule‐associated protein highly expressed in cerebellar Purkinje cells; its knock out in a mouse model causes ataxia. We propose MTCL1 as a candidate gene for autosomal recessive cerebellar ataxia in humans.